Livelihood strategies and entrepreneurs' achievements: A study among successful entrepreneurs participated in KEDA entrepreneurship development programme - Hassan, Kalthum (2013)
The objectives for this study are to discover the livelihood strategies of rural women entrepreneurs to ensure continued success of their businesses and to analyze the relationship between their achievement and their livelihood strategies.The method adopted for this study is qualitative research.A set of semistructured questions was prepared for this purpose.Ten respondents among economically successful participants who engaged with a loan scheme that provides essential equipments for various products proposed by the potential borrowers offered by KEDA (Kedah Development Authority) were interviewed.Even though in theories, respondents who have gone through two entrepreneurship trainings should be able to manage her business successfully,,however, in reality not all participants are successful. The findings show that to succeed the respondents have to have systematic livelihood strategies, well calculated risk and several back-up plans. The respondents also have to have systematic daily routines to properly manage both their households and businesses.A good marketing system for their products is also essential to ensure continued success of their businesses.Based on previous experience of most respondents, there is a strong relationship between livelihood strategies and their business achievements.Systematic livelihood strategies contribute to systematic business management.In addition, the study discovers that strict business management system and close monitoring of business situation help prevent accumulations of long term business problems and ensure long term respectable business achievement.